Everything, everything [book club bag] - Yoon, Nicola (Delacorte Press, 2015)
"The story of a teenage girl who's literally allergic to the outside world. When a new family moves in next door, she begins a complicated romance that challenges everything she's ever known. The narrative unfolds via vignettes, diary entries, texts, charts, lists, illustrations, and more"--